Effect of integrated use of manure and fertilizer on the growth and yield of potato (Progressive Agriculture, 2017)
An experiment was set up in the Research Farm of Patuakhali Science and Technology University, during the rabi season of 2015 to evaluate the effect of fertilizers and manures on the growth and yield of Potato. The experiment was laid out in a Randomized Complete Block Design (RCBD) with two potato varieties namely Diamant (V1) and Cardinal (V2) and five different types and rates of organic manures and inorganic fertilizers viz. T0: Control , T1: NPK, T2: NPK + CW(Cowdung), T3: NPK+ PM(Poultry Mannure) and T4: CW(Cowdung), + PM(Poultry Mannure)  were used for the present study. The twofactor experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Result showed that almost all the characters were affected significantly due to the effect of varieties, organicinorganic fertilizer and their combinations .In case of treatments, NPK with PM also showed the tallest plant (39.76 cm), highest fresh and dry weight (95.97 and 6.05 g plant1, respectively), CGR and RGR (0.086 and 0.218 g m2 day1, respectively), gross (24.36 t ha1) and marketable (23.39 t ha1) compared other treatments. In case of interaction, the highest plant height (41.00 cm), highst fresh and dry weight (96.87 and 3.62 g plant1, respectively), highest CGR and RGR (0.089 and 0.228 g m2 day1, respectively) as well as the highest gross (24.45 t ha1) and marketable (23.67 t ha1) yield were recorded in Diamant at NPK with PM. From the above observation it may be concluded that the variety Diamant at NPK + PM was more effective under Patuakhali region.Progressive Agriculture 27 (4): 435-443, 2016